PEMANFAATAN LAHAN DESA SEBAGAI SARANA PENDIDIKAN KREATIF UNTUK ANAK-ANAK DESA PARIK SABUNGAN - Sosmiarti Sosmiarti; Masri Girsang (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2019)
Parik Sabungan Village, Dolok Pardamean District, Simalungun Regency, North Sumatra has such a large land; this village is the village with the highest population at the Dolok Pardamean sub-district, has the youngest generations and has the potential to be used as agro-tourism. Parik Sabungan Village is still full of customs, culture, and habits instilled from their previous ancestors; one example is village children who have to help their parents to the fields and do not get additional education and creativity and creativity with the children. Other villages. This activity aims to improve community education, especially the younger generation of Parik Sabungan village. The method used island exploration, land preparation, implementation socialization, and technical discussion on the nature school's continuation. This activity aims to improve community education in creative ways by utilizing existing land without incurring high costs. Suggestions for additional activities are to prepare human resources, land, and natural school equipment more optimally so that the nature school can develop and continue to run even though the team has finished carrying out activities in the village.